2021
DOI: 10.3390/soc11020058
|View full text |Cite
|
Sign up to set email alerts
|

COVID-ized Ethnography: Challenges and Opportunities for Young Environmental Activists and Researchers

Abstract: This article offers a critical and reflective examination of the impact of the enforced 2020/21 COVID-19 lockdown on ethnographic fieldwork conducted with UK-based young environmental activists. A matrix of researcher and activist challenges and opportunities has been co-created with young environmental activists using an emergent research design, incorporating a phased and intensive iterative process using online ethnography and online qualitative interviews. The article focuses on reflections emerging from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Four studies explored the effect of COVID-19 on activisms using ethnographic methods, a research approach where researchers use engaged observation of people in their cultural setting to produce a narrative account of that setting. Arya and Henn (2021) used auto-ethnography, a method where the researcher's personal experience is used to describe and interpret community experiences, beliefs, and practices. The authors coproduced a matrix of challenges and opportunities of COVID-19 and related regimes of control for young environmental activists and researchers.…”
Section: Qualitative Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies explored the effect of COVID-19 on activisms using ethnographic methods, a research approach where researchers use engaged observation of people in their cultural setting to produce a narrative account of that setting. Arya and Henn (2021) used auto-ethnography, a method where the researcher's personal experience is used to describe and interpret community experiences, beliefs, and practices. The authors coproduced a matrix of challenges and opportunities of COVID-19 and related regimes of control for young environmental activists and researchers.…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Overall, these studies showed how-while the pandemic did not negatively affect the interest and engagement of activists in these social causes, the health concerns and regulatory restrictions associated with traditional, face-to-face forms of protest led to the proliferation of alternative (mainly online) forms of engagement. In studying environmental activism in the UK, Arya and Henn (2021), showed that the pandemic crisis posed problems but was also a source of new possibilities. For instance, the increased use of online spaces on the one side caused worry about surveillance and police infiltration in the activism activities, but on the other side provided more opportunities for participation for those living in rural areas.…”
Section: Impact Of the Pandemic On Pre-established Activist Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these settings, events offer their heterogeneous groups of participants rare, if not the only, occasions to meet in person, directly interact and recognize each other as stakeholders in the same transdisciplinary action fields. This mode of transdisciplinary exchange and research has changed since March 2020 as we are now observing and participating in virtual events ( Arya and Henn, 2021 ; Howlett, 2021 ; Kim et al, 2021 ; Lupton, 2021 ; Vadrot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…without mobilizing new empirical information). Table 1 summarizes some characteristics of the published manuscripts [25][26][27][28][29][30][31][32][33]. In any case, and whatever the developments in the post-COVID 19 world, it is critical to consider individual and/or collective inequalities of various kinds, and materialized in numerous ways [1,7,[34][35][36].…”
mentioning
confidence: 99%